Selected environmental statistics (The Bureau ParamariboSR, 2002)
Presents statistics on the socio-economic background and sectors such as climate; tourism; transport; environmental health; water; energy; forestry; air; coastal and marine resources; mining; land use and agriculture; and, biodiversity.
Keywords: ENVIRONMENTAL STATISTICS